2014
DOI: 10.1186/s12879-014-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations associated with influenza and respiratory syncytial virus among patients attending a network of private hospitals in South Africa, 2007–2012

Abstract: BackgroundInfluenza and respiratory syncytial virus (RSV) infection are common causes of lower respiratory tract illness. Data on their burden in low and middle-income settings and from Africa are scarce. We aimed to estimate age-specific rates of hospitalization attributable to influenza and RSV among patients attending private hospitals in South Africa during 2007–2012.MethodsWe estimated annual age-specific rates of influenza- and RSV-associated hospitalization (that is respiratory hospitalizations likely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 40 publications
5
45
1
Order By: Relevance
“…This is consistent with Nair et al’s finding that the global burden of illness attributable to influenza in young children is substantial [12]. A study in South Africa found that children aged <1 year and adults aged >75 years had the highest rates of influenza-associated respiratory hospitalization estimated at 255 per 100,000 person-years and 380 per 100,000 person-years, respectively [13]. Similarly, Emukule et al estimated the annual incidence of hospitalized influenza-associated SARI among children aged <5 years in Kenya to be between 180 and 390 cases per 100,000 person-years [14].…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with Nair et al’s finding that the global burden of illness attributable to influenza in young children is substantial [12]. A study in South Africa found that children aged <1 year and adults aged >75 years had the highest rates of influenza-associated respiratory hospitalization estimated at 255 per 100,000 person-years and 380 per 100,000 person-years, respectively [13]. Similarly, Emukule et al estimated the annual incidence of hospitalized influenza-associated SARI among children aged <5 years in Kenya to be between 180 and 390 cases per 100,000 person-years [14].…”
Section: Discussionsupporting
confidence: 88%
“…Specifically in a study conducted in South Africa, influenza virus was detected in 5.8% of patients hospitalized with respiratory illnesses that did not meet the SARI case definition 25. Last, ecological studies have suggested that influenza virus is responsible for hospitalizations and deaths also among patients presenting with circulatory illnesses or even syndromes different than respiratory and circulatory 23, 26. In addition, individuals that may have developed influenza‐associated severe respiratory illness, but did not seek care, would have been missed in our study; hence, our estimates should be considered minimum estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in a study conducted in South Africa, influenza virus was detected in 5.8% of patients hospitalized with respiratory illnesses that did not meet the SARI case definition 24. In addition, ecological studies have suggested that influenza virus is responsible for hospitalizations and deaths also among patients presenting with circulatory illnesses or even non‐respiratory and non‐circulatory syndromes 5, 6, 19. Third, we did not collect data on the total number of medical hospitalizations, hindering our ability to estimate the proportional contribution of SARI‐associated admissions among any medical admission.…”
Section: Discussionmentioning
confidence: 99%